DAMPAK PROMOSI, HARGA, DAN DIFERENSIASI PRODUK DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN - Herman Sjahruddin; Syaiful Akbar (JURNAL ADMINISTRASI & MANAJEMEN, 2020)
This study explores the effect of promotion, price, and product differentiation on purchasing decisions. in this research is amanda brownie product. The population in this study were consumers of Brownis Amanda outlet in Makassar. Sampling used accidental sampling with a determination of time for 2 weeks, so that within that time 96 consumers were obtained as the unit of analysis. The quantitative approach is used through the use of multiple regressions using SPSS Statistics 25. The results of descriptive analysis provide evidence that durability is the most important indicator of product differentiation, appropriateness of the most important suggestions for promotion and affordability of prices are dominant indicators of price and evaluation of alternatives for purchasing decisions. The test results provide evidence that the more intense the promotions carried out and the higher the differentiation of the products, the real impact on the consumer's decision to make a purchase, on the other hand, it is proven that low prices result in high purchasing decisions.